A Technique: Generating Alternative Thoughts - Serkan AKKOYUNLU; M. Hakan TÜRKÇAPAR (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Introduction: One of the basic techniques of cognitive therapy is examination of automatic thoughts and reducing the belief in them. By employing this, we can overcome the cognitive bias apparent in mental disorders. Despite this view, according to another cognitive perspective in a given situation, there are distinct cognitive representations competing for retrieval from memory just like positive and negative schemas. In this sense generating or strengthening alternative explanations or balanced thoughts that explain the situation better than negative automatic thoughts is one of the important process goals of cognitive therapy. Objective: Aim of this review is to describe methods used to generate alternative/balanced thoughts that are used in examining automatic thoughts and also a part of automatic thought records. Alternative/balanced thoughts are the summary and end point of automatic thought work. In this text different ways including listing alternative thoughts, using examining the evidence for generating balanced thoughts, decatastrophizing in anxiety and a meta-cognitive method named two explanations are discussed. Different ways to use this technique as a homework assignment is also reviewed. Remarkable aspects of generating alternative explanations and realistic/balanced thoughts are also reviewed and exemplified using therapy transcripts. Conclusion: Generating alternative explanations and balanced thoughts are the end point and important part of therapy work on automatic thoughts. When applied properly and rehearsed as homework between sessions, these methods may lead to improvement in many mental disorders. [JCBPR 2013; 2(1.000): 53-59]